2022
DOI: 10.1002/acr.24591
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Taking Medications for Systemic Lupus Erythematosus: A Qualitative Study of Racial Minority Patients, Lupus Providers, and Clinic Staff

Abstract: Objective Underrepresented racial and ethnic minorities are disproportionately affected by systemic lupus erythematosus (SLE). Racial and ethnic minorities also have more severe SLE manifestations that require use of immunosuppressive medications, and often have lower rates of medication adherence. We aimed to explore barriers of adherence to SLE immunosuppressive medications among minority SLE patients. Methods We conducted a qualitative descriptive study using in‐depth interviews with a purposive sample of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Another study from New Zealand [ 17 ] provided implications that addressing patients’ concerns about side-effects may improve the relationship between the treating physician and the patient and thereby improve adherence. As in our study, results from other qualitative interview studies [ 18 , 19 , 20 , 21 , 22 , 23 ] suggested that improvements in communication between physicians and patients, making medications affordable and available, increasing the patients’ knowledge about the disease and therapeutic options, challenging the patients’ beliefs regarding medication effectiveness with well-documented evidence as well as facilitating access to healthcare, all are crucial factors that can be expected to contribute to increasing medication adherence.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Another study from New Zealand [ 17 ] provided implications that addressing patients’ concerns about side-effects may improve the relationship between the treating physician and the patient and thereby improve adherence. As in our study, results from other qualitative interview studies [ 18 , 19 , 20 , 21 , 22 , 23 ] suggested that improvements in communication between physicians and patients, making medications affordable and available, increasing the patients’ knowledge about the disease and therapeutic options, challenging the patients’ beliefs regarding medication effectiveness with well-documented evidence as well as facilitating access to healthcare, all are crucial factors that can be expected to contribute to increasing medication adherence.…”
Section: Discussionsupporting
confidence: 70%
“…Overall, our findings concurred with suggestions for interventions against medication non-adherence derived from previous studies involving patients with SLE [ 2 , 41 , 42 ] and other chronic diseases [ 43 ]. Several previous studies have described methods for enhancing adherence to medications in patients with SLE [ 16 , 17 ], some of which were qualitative studies (e.g., from Jamaica, Portugal, the United Kingdom (UK), and the United States (US)) [ 18 , 19 , 20 , 21 , 22 , 23 ], while others explored and evaluated specific interventions in patient groups [ 44 , 45 , 46 , 47 ]. Improved communication between the healthcare and patients along with increased information about the rationale for taking the medication as well as less complicated medication regimens improved adherence in an American study [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al classified medication barriers according to components of the Capability, Opportunity, Motivation, Behaviour change theory. 15 A recent study highlighted that effective patient-physician communication and understanding patients' desires and suggested strategies could improve medication adherence. 8 Building on this work, an intervention was developed based on the key domains of two gold-standard general adherence interventions (Medication Adherence Self-Report Inventory-Visual analogue scale and Brief Medication Questionnaire).…”
Section: Lupus Science and Medicinementioning
confidence: 99%
“…We developed six semi-structured virtual focus groups; four patient focus groups and two healthcare advisor focus groups. The interview guide was developed based on a literature review of patients' and providers' experiences with HCQ and other medications, [13][14][15] and by adapting a focus-group guide used in a prior study on smoking cessation in patients with autoimmune diseases and communication in paediatric diabetes clinics. 23 24 Leveraging blueprints from our team's prior qualitative work 23 and expert facilitators, we planned an onboarding session and a series of four meetings for continuous stakeholder engagement.…”
Section: Data Collectionmentioning
confidence: 99%